Review of Thomas F. Heck. 1999. Picturing Performance: The Iconography of the Performing Arts in Concept and Practice. Rochester: University of Rochester Press - Russano Hanning, Barbara (Current Musicology, 2000)
One picture is worth a thousand words. Despite all the caveats and cautionary tales included in this collection of essays entitled Picturing Performance, the authors convincingly convey their belief that iconography is an invaluable critical tool. During the course of separate contributions by six different specialists, scholars are repeatedly urged to pursue the investigation and proper application of visual sources, are provided with very specific guidelines, and are appropriately reminded that interdisciplinary cooperation is essential in the interpretation of images of the performing arts. Organized and edited by Thomas Heck, Professor of Musicology and head of the Music and Dance Library at Ohio State University, the book presents, as its subtitle promises, essays in the theory and practice of the iconography of the performing arts.